The effectiveness of access to justice in Brazil (International Seven Journal of Multidisciplinary, 2023)
This paper seeks to present some of the elements related to the origin of the concept of access to justice in the Brazilian legal system, to discuss at what stage of effectiveness this right is available to citizens, as well as to outline an analysis of some of the reasons that are indicated in the literature as being responsible for the ineffectiveness of this guarantee. This paper closes by presenting some new developments and improvements in the judicial framework and other areas to facilitate access to justice for citizens. This research took a qualitative and descriptive approach, using bibliographical research in books, articles and legal journals.